Quality of Service at Primary Cooperative Kartika Sumedang - Ressa Ferdiyanti Hidayat; Teguh Santoso; Jajang Supriatna (Journal of Bussines Management Basic, 2022)
The focus of this study is to analyze the quality of service at the primary cooperative Kartika Sumedang which includes 5 dimensions, namely Reliability, Physical Evidence (Tangible), Responsiveness (Responsiveness), Assurance (Assurance), and Empathy (Empathy). The purpose of this study is to determine the quality of service at the Kartika Sumedang Primary Cooperative and to determine the efforts to improve the quality of its services. The method used in the preparation of this thesis is descriptive research with a qualitative approach using primary and secondary data. Primary data was obtained by data collection techniques through interviews and observations, while secondary data came from the primary documents of the Kartika Sumedang Cooperative. In analyzing the data that has been obtained, the Miles and Huberman model with steps; data collection, data reduction, data display, and conclusion drawing/verification data. The method used for the validity of the data is to use the tringulation technique. The results of this study indicate that the application of service quality to the Primary Cooperative Kartika Sumedang has not been fully maximized, especially in the indicator of a comfortable parking space in the dimensions of existing physical evidence (tangible).